Structure and Expression of Two Sex-Related dmrt Genes in Oxyeleotris lineolata - Jiajia FAN; Dongmei MA; Huaping ZHU; Minghui LIN; Zaixuan ZHONG; Yuanyuan TIAN (Progress in Fishery Sciences)
Oxyeleotris lineolata is a valuable economic fish cultured in Australia and countries of Southern Asia. It exhibits sex-related growth dimorphism; the males grow faster and have larger body size than females. Therefore, the efficient development of sex control breeding will be helpful to increase the yield and output value. However, the molecular mechanism regarding sex determination and gonadal differentiation of O. lineolata is poorly understood. Doublesex and mab-3 related transcription (DMRT) factors are known for their contributions in sex determination and differentiation. In this study, the Oxldmrt1 and Oxldmrt3 cDNA sequence was obtained from gonad transcriptome of O. lineolata, identified using PCR. The open reading frame (ORF) of Oxldmrt1 and Oxldmrt3 were 903 bp and 1 363 bp, encoding 300 and 453 amino acids, respectively. OxlDMRT1 belongs to basic proteins, whereas OxlDMRT3 belongs to acidic proteins. The two genes contain a highly conserved DM domain, and OxlDMRT3 also has a DMA domain. Phylogenetic analysis showed that OxlDMRT1 belonged to the DMRT1 family and OxlDMRT3 belonged to the DMRT3 family. The different DMRT families in vertebrates were clustered independently, with the DMRT1 family clustering first followed by the DMRT3 family. The expression levels of two genes in eight tissues of male and female fish were analyzed using RT-qPCR. The results showed that the expression levels of two dmrt genes were most highly expressed in the testis. The expression profiles of two dmrt genes at different developmental stages were analyzed using RT-qPCR. The results showed that the expression levels of two genes were highest in fertilized eggs, the expression level of Oxldmrt1 was the lowest in the optic capsule stage, and Oxldmrt3 was the lowest in the seven days post hatching. The expression and localize of the two genes in the testis were analyzed using fluorescence in situ hybridization (FISH). The results showed that the expression location of the two genes in the testis were identical, and both had strong expression signals in the spermatogonia. In conclusion, Oxldmrt1 and Oxldmrt3 are important in the early embryonic stage and testis development. Oxldmrt1 may also participate in regulating sex determination and differentiation in the late embryonic stage. Oxldmrt3 may also be involved in nervous system development. This study lays a foundation for the molecular mechanism of sex determination and sex differentiation in O. lineolata.